Degree Completion at British Columbia’s Universities - Dennison, John D.; Forrester, Glen C.; Jones, Gordon (Canadian Journal of Higher Education, 1982)
This study investigated an important dimension of the performance of students in two of the universities in British Columbia. Specifically, it examined rates of degree completion, time taken to earn the degrees and the final academic standing attained by graduates. The study involved all students who enrolled between 1973 and 1978, both directly from secondary school and as transfer students from the community colleges in the province. Results were reported by faculty, by department in which students majored, and by sex. The results revealed wide variations by faculty and department. Furthermore, results were not consistent between the two universities concerned. For example, female students performed far better than males at one university but not at the other. Finally, the study exposed many differences in performances between direct entry and transfer students, but again, the differences varied by university and faculty. Finally, the study invited both speculation and further research on the reasons for the inconsistent results. Particular attention was drawn to the need to assess the impact of rising admission standards upon students' withdrawals, degree completion rates and final academic standing.